Variació lèxica. De la idiosincràsia al tractament sistemàtic de la diversitat - Lorente Casafont, Mercè (Caplletra. Revista Internacional de Filologia, 1998)
Several attempts to describe and explain lexical regularities and irregulaties have been made in morphology and semantics. Dialectology and historical grammar have studied phenomena of lexical alternation and change. Yet, applied linguistics has not shown the intrinsic variation of lexic even though there have been, and are, many pedagogical, computer, and lexicographic reasons to describe this complexity. Studies focusing on this issue of variation are relatively recent. There is no grammatical model to thoroughly explain communicative competence available at this point in time. And the incorporation of lexical variation in some theoretical models is still very limited. This paper aims at considering the notion of internal variation as an integral part of the models on the lexical component of grammar. And it also aims at systematically relating the several aspects of lexic with the notion of internal variation.